Exploring the Intention Purchase of Halal Food Products: Evidence from Indonesian Non-Muslim Consumers - Vemy Suci Asih; Elsa Yulandri; Dudang Gojali; Dadang Husen Sobana; Setiawan (Journal of Business Management and Islamic Banking, 2023)
Research Aims:  It is necessary to know what factors attract non-Muslims to consume halal food products so that the right marketing strategy is obtained to expand that market. Research Method: The approach used is descriptive quantitative, multiple regression analysis. The characteristics of the study sample are Indonesian non-Muslims. Data was obtained through questionnaires, with a sample of 180 respondents. Research Findings: The results of the study show the variables that influence the intention to purchase halal products are product ingredients, product safety, and subjective norms. Product awareness does not affect the intention to purchase non-Muslim halal products. Originality: There is no research that discusses the factors that influence purchase intention, with a sample of Indonesian non-Muslims, and with the same variables as this study. Implication: Halal food products are available and can be consumed by Muslim and non-Muslim communities, so halal products have great potential to continue to grow.